(untitled) (Archive of Conferences, 2020)
In this article studied the decisions of linguistic aspects of phraseological units characterizing a person in English language, as well as the detection of the regularities of particular phraseological group integrations in which different by its structure and the semantics of phraseological units with the concept «person»